AKUNTABILITAS PELAYANAN PUBLIK DI KANTOR SAMSAT KOTA JAYAPURA - rahmat, Rahmat Nurjaman (Jurnal Administrasi Publik dan Pemerintahan, 2025)
This research aims to describe the accountability aspects of public services at the Samsat office in Jayapura City, Papua in serving taxpayers in a transparent, safe and open manner. includes service processes, service costs, and service products. This research uses descriptive qualitative research. This research instrument consists of an interview guide and documentation study. The information was taken from policy-making elements at the Jayapura City Samsat office and stakeholders who really know or actors who are directly involved in the problem. To measure the accountability of public services using the dimensions (Sutrisno 2009) of effectiveness, efficiency, responsiveness, legal certainty and transparency. Data analysis techniques using interactive models, data reduction, data presentation and drawing conclusions. From research results. The vehicle tax fine exemption program in Jayapura City has not shown positive results. From the research results. Based on the results of the analysis of public service accountability indicators, it can be concluded that the Jayapura City Samsat Office has shown quite good performance in providing services to the community. The spread of service points in various places and technology-based innovation increases effectiveness and efficiency. The responsiveness of services can be seen from the various programs provided, while legal certainty and financial transparency indicate good governance. However, there are several aspects that can still be improved, such as optimizing the achievement of revenue targets from Motor Vehicle Transfer of Title Fees and increasing access to service information for the public. Keywords: Accountability, Public Services, Samsat, Jayapura.